The physiological responses to volume-matched high-intensity functional training protocols with varied time domains - Smith, J. S.; Bellissimo, G. F.; Amorim, F. T. (Frontiers in Physiology, 2025)
Background: High-intensity functional training (HIFT) is typically performed with minimal or no rest periods, including "rounds for time" (RFT) or "as many rounds or repetitions as possible" (AMRAP) design. Alternatively, some HIFT workouts can be performed with prescribed rest intervals (e.g., "every minute on the minute" [EMOM]) that may have significant effects on physiological responses.